Sintesis lempung montmorillonit terpilar Fe2O3 dan kajian sifat-sfat kimia fisiknya=Synthesis of Fe2O3 pillared montmorillonite clay and study of its physico-chemical properties - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2004)
It has been studied in this work the change of physical and chemical properties of Fe203-pillared clay. The pillared clay has been synthesized by intercalating polyoxycation of the iron into the interlayer of the montmorillortite clay. The intercalated compound then was calcinated at various temperature. They were 100°C, 150°C, 200°C, 250°C, and 300°C to obtain Fe203-pillared clay. The observed properties were basal spacing door, specific surface area, pore-size distribution, total pore volume, adsorption isotherm and surface acidity. The basal spacing door was determined by X-ray diffraction method, specific surface area, average pore radius, total pore volume and adsorption isotherm were analyzed by Gas Sorption Method Analysis, and surface acidity measured by gravimetric and FTIR Spectroscopic methods. The result of characterization showed that the basal spacing clan increament of Na-montmorillonite, Fe-PILCioo, Fe-PILC150, FePILC2oo, Fe-PILC23o, and Fe-PILC3oo were 6.05A, 7.99A, 22.97 A, 6.51A, and 10.18A, respectively. The specific surface area of Namontmorillonite, Fe-PILCtoo, Fe-PILCiso, Fe-PILC200, Fe-PILC2so, and Fe-PILC300 were 90.0587 m2/ g, 155.0751m2/g, 164.0924m2/g, 170.5416m2/g, 161.1349m2/g and 144.3453m2/g, respectively.The pore-size distribution is bimodal. The total pore volume of Namont and Fe-PILC were 0.06092 cc/ g and 0.12626 cc/ g to 0.15450 cc/ g. The N2 adsorption isotherm on Fe203 (Fe-PILC) are of type IV in the BDDT classification indicating that these pillared clay have both micropore and mesopore. The surface acidity of Namontmorillonite and Fe203 pillared clay were 0.5096 mmol/ g and 2.8498 mmol/ g to 7.0515 mmol/ g, respectively. Determination of Fe content showed that the average content of Fe203-Pillared Clay was 23,46 % w/w.